(untitled) (Baghdad Science Journal, 2025)
New metal complexes of some transition metal ions Co(II), Cu(II) , Cd(II) and Zn(II) were prepared by their reaction with previously prepared ligands HLI= (P-methyl anilino) phenyl acetonitrile and HLII = (P-methyl anilino) –P– chloro phenyl acetonitrile . The two ligands were prepared by Strecker’s procedure which includ the reaction of p- toluidine with benzaldehyde and P- chlorobenzaldehyde respectively. Structures were proposed depending on atomic absorption , i.r. and u.v.visible spectra in addition to magnetic susceptibility and electrical conductivity measurements.